Aspiration of Rural Youth Towards Agriculture (Indian Journal of Extension Education, 2019)
Rural youth are very important segment of the rural society and they play a vital role in agriculture and rural development. The present study was conducted in the twelve villages of four Panchayat Samities of Akola and Amravati districts in Maharashtra State. An exploratory design of social research was used for the study. The finding revealed that the overall aspiration of the rural youth (49.17%) towards agriculture had medium level of aspirations, whereas, 33.33 and 17.50 per cent of the rural youth had low and high level of aspirations, respectively. Majority (47.73%) of the rural youth about horticulture had medium level of aspiration. With regards to dairy farming the majority (57.69%) of the rural youth had medium level of aspiration. Education, land holding, annual income, mass media exposure, extension contact, extension participation, achievement motivation, economic motivation and innovativeness were found to be significantly correlated with the aspiration of the rural youth about agriculture. With regards to horticultural activities, the variables like education, land holding, extension contact, extension participation, achievement motivation, economic motivation and innovativeness were found significantly correlated with the aspiration of the rural youth. Regarding dairy farming activities, variables like education, land holding, annual income, mass media exposure, extension contact, extension participation, achievement motivation, economic motivation and innovativeness were found to be significantly correlated with the aspiration of the rural youth.